Information Needs in Engineering - Visvesvaraya, H. C. (Journal of Information and Knowledge, 1978)
Discusses the value of information in general. Highlights engineering information as an ensemble subsuming scientific information and management and social sciences information. Refers to the magnitude of information explosion and information utilization and analyses the categories of information needs. After discussing the paucity of information systems in engineering at the international level and in India, points out the vitality of technology transfer interface system for industrial information. The integrated approach to industrial information of the Cement Research Institute of India is described. The obstacles to documenting engineering information are also mentioned. Suggests bilateral programmes for improving engineering information services.